A new analytical method to optimise the preventive maintenance interval by using a semi-Markov process and z-transform with an application to marine diesel engines. (March 2021) - Sánchez-Herguedas, Antonio; Mena-Nieto, Angel; Rodrigo-Muñoz, Francisco
Highlights: A new analytical method to calculate the preventive interval is proposed. The preventive interval is the time that maximises the returns (income minus costs). A semi-Markov process approach has been developed to model the returns. The z-transform is used as a tool to solve the resulting difference equations system. A real case study of the marine diesel engine is used to apply this analytical method. Abstract: This article presents a novel method based on a semi-Markov process approach and the z transform to calculate the optimal time interval until the preventive maintenance intervention. For this, a mathematical expression that has its origin in the evolution of the maintenance cost of a patrol boat's propulsion engine is developed, represented mathematically by a system of difference equations. This method can be applied to all assets that are subject to wear, which are very common on industrial facilities. This mathematical expression for the preventive interval is a powerful tool for maintenance managers because this saves him from resorting to complicated mathematical methods. In addition to the proposed mathematical formula, the manager needs to know the assets' failure history data and the costs of maintenance interventions. These data are usually available, making their practical application fast and easy to develop. Due to the method being analytical, it could also serve as an excellent decision support tool. It can be applied to the desired time horizon guaranteeing the obtention of the optimal interval. In many other cases, applying the model can simplify the process of obtaining the asset maintenance programme, from an economic perspective. Graphical abstract: Image, graphical abstract